An ethnographic exploration of diarrheal disease management in public hospitals in Bangladesh: From problems to solutions. (September 2020) - Biswas, Debashish; Hossin, Raduan; Rahman, Mahbubur; Bardosh, Kevin Louis; Watt, Melissa H.; Zion, Mazharul Islam; Sujon, Hasnat; Rashid, Md Mahbubur; Salimuzzaman, M.; Flora, Meerjady S.; Qadri, Firdausi; Khan, Ashraful Islam; et al.
Abstract: Introduction: Diarrheal disease is one of the most common causes of hospital admission globally. The barriers that influence guideline-adherent care at resource limited hospitals are poorly defined, especially during diarrheal disease outbreaks. The objective of this study was to characterize challenges faced in diarrheal disease management in resource-limited hospitals and identify opportunities to improve care. Methods: The study was conducted during a diarrheal disease outbreak period at ten public district hospitals distributed across Bangladesh. A rapid ethnographic approach included observations and informal interviews with clinicians, staff nurses and patients. In the first phase, observations identified common and unique challenges in diarrheal management at the ten sites. In the second phase, four hospitals were purposively selected for additional ethnographic study. Systematic observations over 420 total hours were collected from patient-clinician interactions (n = 76) and informal interviews (n = 138). Applied thematic analysis identified factors that influenced hospitalbased diarrhea management. Results: Normalization of guideline deviation was observed at all ten sites, including prescription of non-indicated antibiotics and intravenous (IV) fluids. Conflict between 'what should be done' and 'what can be done' was the most common challenge identified. Clinical assessments and patient treatment plans were established at admission in a median of 2 minutes (n = 76), often without a physical examination (57%; n=43/76). Factors that prevented adherence to clinical guidelines included human resource constraints, conflicts of interests, overcrowding, and inadequate hygiene and sanitation in the emergency department and wards. Conclusion: This study identified challenges in hospital-based management of diarrheal disease and opportunities to improve care in seemingly change-resilient hospital settings. The results reveal important areas for intervention and policy engagement that may have additive benefit for both hospitals and their patients. These interventions include targeting barriers to clean-water, sanitation and hygiene that prevent clinicians from adopting guidelines out of concern for hospital acquired infections. Highlights: There are opportunities to improve diarrheal disease management in seemingly change-resilient hospital settings. Improving sanitation and hygiene may increase guideline adherence by reducing concern for hospital-acquired infections. Human resource constraints, conflicts of interests and overcrowding expand the gap between knowledge and action.